Milk supply and breastfeeding decisions: the effects of new mothers’ experiences - Amy Brown (NCT Perspectives, 2015)
In the UK significant numbers of mothers stop breastfeeding in the early weeks, typically before they are ready, commonly citing poor milk supply. This review considers how the physiological issue of poor milk supply can often be explained by psychological, social and cultural factors rather than biological impediment. It unpicks how, whilst biological inability to breastfeed should affect a very small minority of women, considerable numbers of new mothers report insufficient breastmilk supply, ultimately leading to a decision to stop breastfeeding.This article aims to provide an overview of:• how breast milk supply is established;• the difference between primary physiological inability to breastfeed and poor milk supply as a result of feeding experience;• the layers of psychological, social, and cultural factors that affect milk supply and hence infant feeding decisions; and• messages for breastfeeding support.